Misuse of the Term Retrospective Cohort. Comment on Alsayouf et al. Atomoxetine Treatment of Attention Deficit/Hyperactivity Disorder Symptoms in 3–6-Year-Old Children with Autism Spectrum Disorder: A Retrospective Cohort Study. Children 2024, 11, 163 - Mehran Zarghami (Children)
Recently, an article entitled “Atomoxetine Treatment of Attention Deficit/Hyperactivity Disorder Symptoms in 3–6-Year-Old Children with Autism Spectrum Disorder: A Retrospective Cohort Study” was published in the journal Children. In this letter, the methodology of the mentioned study is discussed.